Implementation of genomic selection in the poultry industry. (1st January 2016) - Wolc, A.; Kranis, A.; Arango, J.; Settar, P.; Fulton, J.E.; O'Sullivan, N.P.; Avendano, A.; Watson, K.A.; Hickey, J.M.; de los Campos, G.; Fernando, R.L.; Garrick, D.J.; et al.
Abstract: This paper describes and discusses implementation of genomic selection in broilers and layers, emphasizing distinctive features of the poultry industry. We discuss various practical aspects of implementation, from development of tools and calculation of costs from the experimental stage up to actual implementation in commercial settings. Experimental implementations have shown that genomic data can indeed be used to improve the accuracy of estimated breeding values and lead to greater response to selection than traditional selection methods. Opportunities to reduce generation intervals are, however, limited, in particular for broiler breeding programs. We also identify several challenges of practical implementation of genomic selection, such as maintaining accuracy with large-scale DNA collection and labeling, genotyping costs, collecting accurate phenotypes for training, and meeting high requirements in terms of data storage and analysis. Currently, genomic selection has been implemented for routine evaluation in the poultry industry, but we are looking forward to further developments in technology, analytical tools for maximizing genetic gain while constraining inbreeding, and costs of running genetic improvement programs in poultry.